2003
DOI: 10.1029/2002wr001597
|View full text |Cite
|
Sign up to set email alerts
|

Testing and parameterizing a conceptual model for solute transport in a fractured granite using multiple tracers in a forced‐gradient test

Abstract: [1] A cross-hole tracer test involving the simultaneous injection of two nonsorbing solute tracers with different diffusion coefficients (bromide and pentafluorobenzoate) and a weakly sorbing solute tracer (lithium ion) was conducted in a fractured granite near an underground nuclear test cavity in central Nevada. The test was conducted to (1) test a conceptual radionuclide transport model for the site and (2) obtain transport parameter estimates for predictive modeling. The differences between the responses o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
165
1
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 132 publications
(172 citation statements)
references
References 26 publications
5
165
1
1
Order By: Relevance
“…With measured porosities of 0.01 to 0.02, the range of effective diffusivity is 1.2 x 10 -13 to 4 x 10 -12 m 2 /s. Interestingly, when fitting a field tracer test, Reimus et al (2003) reported a lumped diffusion term of b D p p ε (where b is the fracture half-aperture). Based on the combination of these values, the fracture aperture ranges from 0.6 to 8 mm.…”
Section: Radionuclide Diffusion Parameters For Granitementioning
confidence: 99%
See 2 more Smart Citations
“…With measured porosities of 0.01 to 0.02, the range of effective diffusivity is 1.2 x 10 -13 to 4 x 10 -12 m 2 /s. Interestingly, when fitting a field tracer test, Reimus et al (2003) reported a lumped diffusion term of b D p p ε (where b is the fracture half-aperture). Based on the combination of these values, the fracture aperture ranges from 0.6 to 8 mm.…”
Section: Radionuclide Diffusion Parameters For Granitementioning
confidence: 99%
“…However, the value of 9 x 10 -12 m 2 /s was calculated using an unrealistically high porosity of 0.045. Reimus et al (2003) reported that laboratory measured pore diffusivities for Shoal granites (Br -experiments) ranged from 1.2 x 10 -11 to 2 x 10 -10 m 2 /s. With measured porosities of 0.01 to 0.02, the range of effective diffusivity is 1.2 x 10 -13 to 4 x 10 -12 m 2 /s.…”
Section: Radionuclide Diffusion Parameters For Granitementioning
confidence: 99%
See 1 more Smart Citation
“…For a thermally degrading tracer, the term -kC must be added to left side of Equation (4.1), and the term -kC m must be added to the left side of Equation (4.2), where k is the decay constant given by Equation (2.1). The transformation of Equations (4.1) and (4.2) to the Laplace domain and their subsequent Laplacedomain solution and inversion of the result back to the time domain are described by Reimus et al (2003).…”
Section: Thermally Degrading Tracers To Predict Thermal Breakthroughmentioning
confidence: 99%
“…Four additional characterization wells were drilled at Shoal during summer and fall 1999; details of the drilling and well installation are in IT Corporation (2000), with testing reported in Mihevc et al (2000). A key component of the second field program was a tracer test between two of the new wells (Carroll et al, 2000;Reimus et al, 2003).…”
Section: Introductionmentioning
confidence: 99%